The right to health: guidance from international human rights law and experience from other countries - Fauzi, Husna (IIUM Press, 2011)
This chapter discuss the right to health from the perspective ofthe Irternational Human Rights Law. It begins with a brief explaination of the concept of health. This is followed by a general discussion on the link betwccn health and human rights and the right 10 health from the perspectives of the international and regional human rights inslrumetlts as well as the right to health as proclaimed in the scb:ted national constitutions